2006
DOI: 10.1299/jsmeb.49.980
|View full text |Cite
|
Sign up to set email alerts
|

Pulsating Flows: Experimental Equipment and Its Application

Abstract: Investigations of time-dependent laminar and transitional flows need accurate and reproducible generation of the flow as a function of time. For this purpose, an electronically controlled air valve, with which the mass flow rate is controlled, was designed and built. The working principle and lay-out of the valve are explained and the performance of the valve is demonstrated. It was found that with the present equipment one can study any non-periodic and periodic flow and the flow can be adjusted to be laminar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Work in this direction is already underway, as some of the parameters described here are being considered in guiding and planning controlled experimental and numerical investigations of pulsatory flow with prescribed pressure or mass flow rates. Examples include those carried out by Ray et al [32], Ünsal and Durst [53], Ünsal et al [54,55], and Durst et al [56].…”
Section: Discussionmentioning
confidence: 99%
“…Work in this direction is already underway, as some of the parameters described here are being considered in guiding and planning controlled experimental and numerical investigations of pulsatory flow with prescribed pressure or mass flow rates. Examples include those carried out by Ray et al [32], Ünsal and Durst [53], Ünsal et al [54,55], and Durst et al [56].…”
Section: Discussionmentioning
confidence: 99%
“…Huelsz and Lopez-Alquicira [75,76] used HWA to measure acoustic velocities in air with frequencies of 35, 46 and 130 Hz and velocity of 0.3-0.8 m s −1 . Ünsal and Durst [77] studied pulsating laminar and transitional pipe flows using HWA. Their laminar flow investigations showed that the generated sinusoidal mass flow rates agreed well with those of the analytical solution.…”
Section: Hot-wire Anemometrymentioning
confidence: 99%
“…Then, the second intermediate velocity u is calculated. The central difference scheme was used for the viscous terms in (16). The pressure profile was calculated by the following Poisson equation:…”
Section: Two-dimensional Simulation For Analyzing Liquid Pipementioning
confidence: 99%
“…Hwang and Brereton [13] and Brereton and Mankbadi [14] investigated turbulent pulsating pipe flows. Eguchi et al [15] measured the velocity distribution of pulsatile flows in a vertical rigid and elastic tube using a PIV measurement technique.Ünsal and Durst [16] studied both fully developed steady pipe flows and pulsating flows with the Reynolds number ranging from 180 to 18000 and a pipe diameter of 15 mm. He and Jackson [17] investigated pulsating turbulent flows in a pipe using a two-component laser Doppler anemometer (LDA).…”
Section: Literature Surveymentioning
confidence: 99%